Revision of Cerozodus Bigot, 1857 (Diptera, Asilidae, Asilinae) with description of a new species from Brazil - Vieira, Rodrigo; Rafael, José Albertino; Limeira-De-Oliveira, Francisco (Zootaxa, 2013)
The second species of the Neotropical genus Cerozodus Bigot, 1857, Cerozodus brachylobus sp. nov. is described from Mirador, Maranhão state, Brazil and Cerozodus nodicornis (Wiedemann, 1828) is redescribed. The habitus, wing and male terminalia structures are described and illustrated.